2018
DOI: 10.1099/ijsem.0.002623
|View full text |Cite
|
Sign up to set email alerts
|

Blautia hominis sp. nov., isolated from human faeces

Abstract: A strictly anaerobic, Gram-stain-positive, non-motile and coccoid- or oval-shaped bacterium, designated strain KB1, was isolated from a faecal sample of a patient with diverticulitis in South Korea. Degeneracies in the 16S rRNA gene sequence of strain KB1 were resolved by cloning, which yielded five different sequences with heterogeneity. Phylogenetic analysis based on the 16S rRNA gene sequences showed that strain KB1 formed a monophyletic branch with species in the genus Blautia, with highest sequence simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The composition of this genus is constantly updated by adding new species and strains, but in general, the species in Blautia still form a relatively stable and coherent uniline branch. 27 According to reports, the human intestinal microbial community can be divided into three "enterotypes," namely, Bacteroides, Prevotella, and Ruminococcus, among which the Ruminococcus type is mostly driven by related groups of the order Clostridiales, Blautia, and unclassified Lachnospiraceae. 31 Blautia is widely distributed in mammalian feces and intestines.…”
Section: Morphological Physiological and Biochemical Characteristics Of Blautiamentioning
confidence: 99%
“…The composition of this genus is constantly updated by adding new species and strains, but in general, the species in Blautia still form a relatively stable and coherent uniline branch. 27 According to reports, the human intestinal microbial community can be divided into three "enterotypes," namely, Bacteroides, Prevotella, and Ruminococcus, among which the Ruminococcus type is mostly driven by related groups of the order Clostridiales, Blautia, and unclassified Lachnospiraceae. 31 Blautia is widely distributed in mammalian feces and intestines.…”
Section: Morphological Physiological and Biochemical Characteristics Of Blautiamentioning
confidence: 99%
“…At the time of writing, the genus Blautia comprises 21 species and 15 validly published species with correct names (www.bacterio.net/Blautia.html). The validly published names are Blautia argi [4], Blautia caecimuris [5], Blautia coccoides [3, 6], Blautia faecicola [7], Blautia faecis [8], Blautia glucerasea [9], Blautia hansenii [3, 10], Blautia hominis [11], Blautia hydrogentrophica [3, 12], Blautia luti [3, 13] , Blautia obeum [14, 15], Blautia producta [3, 10], Blautia schinkii [3, 16], Blautia sterocoris [17] and Blautia wexlerae [3]. B.…”
Section: Full-textmentioning
confidence: 99%
“…These sequenced reference strains (from both official or proposed species) were useful to give a name to each group they represented (Table 1). In one group, we found genomes from representative strains from both official and a proposed species in a same genomic species group: the proposed species "Blautia marasmi" [strain Marseille-P2377, GCF_900258535.1, (Pham et al, 2017a)] was found to be part of the same genomic species group as B. hominis [strain KB1, GCF_002270465.1, (Shin et al, 2018)]. Moreover, we also found that both B. producta and B. coccoides type strains are part of the same genomic species cluster, since their pairwise values reflected this feature.…”
Section: Resultsmentioning
confidence: 99%